Irbesartan Attenuates Sepsis-Induced Renal Injury In Mice Models. (Journal of Pharmaceutical Negative Results, 2022)
Sepsis is the main cause of death following infection and is regarded as a worldwide health problem. Sepsis is a systemic inflammatory side consequence of microbial infection. To investigate any possible reno-protective effects of irbesartan during sepsis-induced renal damage. Forty male albino Swiss mice, weighing 25–30 grams and aged 8–12 weeks, were used in the current investigation. Both food and water were freely available to these animals. Mice were separated into the following four groups after two weeks of adaption. (n = 10): (1) Normal group: apparently healthy mice. (2) CLP group: mice underwent CLP operation. (3) Vehicle group: mice receivedDMSO (4) irbesartan group: mice received irbesartan 3 mg/kg/day intraperitoneally for 5 consecutive days. ) irbesartan group demonstrated a significant (p<0.05) decrease in the renal levels of NGAL as compared to the CLP group. Furthermore, the irbesartan group demonstrated a significant (p<0.05) decrease in the serum level of inflammatory cytokines (TNF-α, IL-6, & IL-1β) as compared to the CLP group. Additionally, the irbesartan group showed a significant (p<0.05) elevation in the renal SOD activity and reduction of MDA level as compared to the CLP group. Histologically, All mice in the CLP group showed a significant (p<0.05) renal tissue injury, while the irbesartan group showed a significant (p<0.05) reduced level of renal tissue injury. The anti-inflammatory effect through their ability to decrease serum levels of inflammatory cytokines (TNF-α, IL-1β, and IL-6). Also the anti-oxidant effect through their ability to decrease renal levels of MDA and increase the renal activity of SOD.